Spatial immune profiling reveals distinct microenvironments in medullary thyroid carcinoma - de Castro, Maria Eduarda; de Siqueira, Gustavo Forlin; Mariano, Jean Ferrante; Kizys, Marina Malta Letro; Ceolin, Lucieli; Soares, Fernando Augusto; Natal, Rodrigo; Carneiro, Humberto; Ramos, Rodrigo Nalio; Ward, Laura Sterian; Camara, Niels Olsen Saraiva; Pinto Camacho, Cleber; et al. (Frontiers in Immunology, 2025)
IntroductionMedullary thyroid carcinoma (MTC) is a rare and aggressive thyroid cancer with a challenging prognosis. While the immune microenvironment plays a crucial role in cancer progression, its role in MTC remains underexplored compared to more common thyroid cancers.Methodsthis study investigates the immune landscape of MTC by systematically evaluating immune cell infiltration and expression of immune markers across various tissue topographies. We utilized advanced immunohistochemical techniques to analyze tissue samples from 24 MTC patients, focusing on the tumor core, interface with healthy tissue, adjacent normal thyroid tissue, and lymph node metastases.Resultsour findings reveal a distinct immune profile with increased CD3+, CD4+, CD8+ and CD20+ lymphocytes in normal tissues adjacent to tumors and a notable presence of granzyme B+ cells in the tumor interface, particularly in patients with structural disease. Additionally, we observed a significant enrichment of mast cells in metastatic tissues.Discussionthese results highlight the complex and spatially dependent immune landscape of MTC, suggesting implications for targeted immunotherapy. This study provides novel insights into the immune microenvironment of MTC and emphasizes the need for further research to elucidate its impact on disease progression and therapeutic response.